Kris Lemsalu : birth V, hi and bye - Lemsalu, Kris, 1985-; Arusoo, Maria (Mousse Publishing, 2019)
The work of Kris Lemsalu is pagan and it's punk and it's hers and it's ours. . . . It's the lightning of heaven and the volcanic heat in the abyssal ocean. It's the carnival of objects Frankensteined together into concoctions as fragile as life itself. It's life.'''Andrew Berardini Kris Lemsalu is an Estonian-born artist who creates mixed-media sculptures, installations, and performances utilizing unexpected materials. Often underscored by feminist themes, her works evoke the bestial side of humanity and civilizations. This book offers a peek into Lemsalu's explorations in art and life, which in her case are inseparable. The rich visual material, selected by the artist herself, ranges from exhibition views; to analog photos of the artist, her friends, and her collaborators; to her everyday work at the studio; to the wild parties she attends. Essays by Los Angeles'based writer Andrew Berardini and Estonian curator and writer Tamara Luuk overview Lemsalu's oeuvre with a particular focus on BIRTH V: Hi and Bye, her biggest project yet, which was co-published by Mousse Publishing and the Estonian Centre for Contemporary Art and produced for the Estonian Pavilion at the 58th Venice Biennale in 2019.00Exhibition: 58th Venice Biennale, Venice, Italy - Estonia Pavilion (11.05-24.11.2019).